2014
DOI: 10.1021/om500306a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic DFT Study on Ethylene Trimerization of Chromium Catalysts Supported by a Versatile Pyrrole Ligand System

Abstract: To elucidate fundamental mechanistic aspects of the landmark Chevron–Phillips ethylene trimerization system, a detailed theoretical study has been carried out by DFT methods on an aluminum pyrrolyl chromium catalyst. Reaction pathways for selective ethylene oligomerization have been successfully located on the basis of the metallacycle mechanism. Consistent with experimental results, for the model system ethylene trimerization was proven to be energetically preferred in comparison to ethylene dimerization or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 39 publications
(89 reference statements)
5
33
0
Order By: Relevance
“…Furthermore, a two-step process that leads to 3 from 2 was also attempted, bearing a first H transfer; however, it was omitted from the analysis since kinetically it was found to be much less efficient. For the parent model system A, the energy profile calculated in Figure 1 is very similar to that calculated earlier by Liu and coworkers [12]. The rate for determining step size (rds) turned out to be the transition state leading to the formation of the 7-membered metallacycle 5A, with an upper barrier placed at 24.9 kcal/mol over intermediate 3A, which is slightly less efficient compared to the previous results of Liu [12].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, a two-step process that leads to 3 from 2 was also attempted, bearing a first H transfer; however, it was omitted from the analysis since kinetically it was found to be much less efficient. For the parent model system A, the energy profile calculated in Figure 1 is very similar to that calculated earlier by Liu and coworkers [12]. The rate for determining step size (rds) turned out to be the transition state leading to the formation of the 7-membered metallacycle 5A, with an upper barrier placed at 24.9 kcal/mol over intermediate 3A, which is slightly less efficient compared to the previous results of Liu [12].…”
Section: Resultssupporting
confidence: 81%
“…For example, there is a compromise that the catalytic cycle is accomplished via the formation of a metallacycle pathway in which the chromium centre operates via a redox Cr(I/III) metallacyclic mechanism [11]. In fact, theoretical studies of the activation energies for different stages of the trimerization process have revealed that the model containing Cr (I/III) redox has lower energy levels than the Cr(II/IV) species, due to greater stability of the oxidation state in the Cr(I/III) system [12]. This finding was further supported by the experimental results from an electron paramagnetic resonance (EPR) investigation on the same catalytic system [13].…”
Section: Introductionmentioning
confidence: 99%
“…For the parent model system A, the energy profile we calculate in Figure 1 is very similar to that 98 calculated earlier by Liu and coworkers [12]. The rate determining step (rds) turns out to be the 99 transition state leading to the formation of the 7-membered metallacycle 5A with an upper barrier 100 placed 24.9 kcal/mol over intermediate 3A, which is slightly more disfavoured with respect to 101 previous results of Liu [12].…”
supporting
confidence: 80%
“…The rate determining step (rds) turns out to be the 99 transition state leading to the formation of the 7-membered metallacycle 5A with an upper barrier 100 placed 24.9 kcal/mol over intermediate 3A, which is slightly more disfavoured with respect to 101 previous results of Liu [12]. The alternative undesired reactions that lead to 8 and 9 are found to be 102 less favoured kinetically by 8.8 and 1.6 kcal/mol, respectively.…”
mentioning
confidence: 77%
“…Even though a catalytic cycle involving cationic Cr I/III species currently prevails, [43][44][45][46][47] a catalytic cycle involving the Cr II/IV species has not been SCHEME 2 Preparation of catalyst precursors bearing [B(C 6 F 5 ) 4 ]-completely excluded. [9,44,48] It was also reported that the majority of the Cr III precursors were converted into EPR-silent Cr II species during the activation process with alkylaluminum. [46,47,49] In the elemental analysis data roughly agreed with the formula (calculated: C 53.50, H 4.34%; found: C 51.20, H 3.41%).…”
Section: Ethylene Oligomerization (Entry 11 Inmentioning
confidence: 99%